Factores de riesgo asociados a prematuridad y las complicaciones respiratorias en el neonato. - España Cuasapaz, Karla Estrella (2023)
Introduction: The World Health Organization (WHO) with a cut-off of 2023 highlights that prematurity and its high rate of morbidity and mortality is due to the lack of viable cost-effective care measures in basic medical care to treat infections and breathing diffciulties. The identified risk factors for premature birth include maternal history of diabetes, obesity, multiple pregnancy, hypertension, maternal low weight, consumption of toxic substances and other chronic diseases. Objective: Determine the highly prevalent risk factors that predispose to prematurity through a review of bibliographic data; during the period 2022-2023. Methodology: the present study focuses on a descriptive methodology, non-experimental documentary design, cross-section that is part of qualitative bibliographic scientific research. Results and Discussion: current Public Health problem with representation of 90% of processes within the first month of life, estimates of 98% in developing countries, to this are added epidemiological, clinical, environmental, and socioeconomic factors. Conclusion: synthesize the scientific evidence in relation to the risk factors that lead to prematurity, among which age stands out as a triggering factor for this situation, with 53.7% occurring in adolescent women determined by their physiological immaturity and 46 .3% in elderly mothers, the age is within the range of 15 to 40 years of age.